Enhanced Influenza Surveillance Utilizing Rapid Diagnostic Tests in the Emergency Department - Janice Caoili; Aliza Concepcion; Monica Joyce Lanuza; Heloisa Nicole Dayap; Maria Reinaluz Bactol (Journal of Global Antimicrobial Resistance)
AIM: To utilize flu rapid test data to monitor flu season and schedule healthcare worker vaccinations. BACKGROUND: In the Philippines understanding the influenza season's timing is challenging due to limited testing capacity. During the COVID pandemic, influenza rapid diagnostic tests gained popularity, assisting Emergency Department (ED) physicians in treatment decisions. Our hospital uses ED influenza data for surveillance METHODS: Daily reporting of ED influenza test results to IPCD RESULTS: Between January 2023 and July 2024, 5,786 ED patients were tested for influenza A and B. 89% used CapiliaTM Flu Neo rapid test and 11% used BIOFIRE RP2.1 Panel.In 2023, overall positivity rate (PR) was 26%: 21% fluA and 4% fluB. Testing increased from June, with 4.3% rise compared to May. June had the highest PR of 41% (28/69), all due to fluA. 78% of patients were tested from October to December, yielding a 26% PR: 23% fluA and 3% fluB.From January-July 2024, overall PR was 18%: 17% fluA and 1% fluB. Flu testing declined initially: PR of 11% in January to 1% in May. June had lowest testing but a 24% PR. Testing increased by 5.3% in July, with 45% PR. Since May 2024, all cases had fluA.In 2024, healthcare worker flu vaccinations began in April, ahead of anticipated rise in cases from June. CONCLUSION: Surveillance revealed year-round influenza presence, cases increased in June and peaked by Oct-Nov, primarily fluA. Most admitted cases were discharged, and mortality rate remained low.